2008
DOI: 10.1002/anie.200803254
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of a Me2Zn/α‐Diimine System: A Unique Zinc Methylperoxide Cluster and Evidence for Its Sequential Decomposition Pathways

Abstract: O what a reaction: The oxygenation of Me2Zn⋅tBu‐DAB (tBu‐DAB=1,4‐di‐tert‐butyl‐1,4‐diazabutadiene) affords the unprecedented oxo(methylperoxide) cubane 1, the corresponding double cubic oxo(methoxide) 2, and the CC coupled dinuclear methoxide [(MeZn)2(tBu‐DAB‐DAB(H)‐tBu)(μ‐OMe)], the formation of which involves initial ZnOOMe bond homolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 38 publications
5
29
1
Order By: Relevance
“…As already noted, the widely accepted mechanism implies that the formation of an alkoxide species is a consequence of a metathesis reaction between the resulting zinc alkylperoxide and the parent alkylzinc compound (Scheme a; metathesis) . Conversely, our results on the oxygenation of 1 and 2 at low temperature, along with earlier reported precedents concerning the oxygenation chemistry of zinc,, aluminum, and particularly magnesium alkyls, stand in clear contradiction to this widely accepted metathesis process. The formation of zinc alkoxides can be rationalized in terms of an intramolecular transformation of zinc alkylperoxides (Scheme ; the proposed η 2 ‐binding mode of alkylperoxide ligand has previously been observed for aluminum and magnesium alkylperoxide complexes).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…As already noted, the widely accepted mechanism implies that the formation of an alkoxide species is a consequence of a metathesis reaction between the resulting zinc alkylperoxide and the parent alkylzinc compound (Scheme a; metathesis) . Conversely, our results on the oxygenation of 1 and 2 at low temperature, along with earlier reported precedents concerning the oxygenation chemistry of zinc,, aluminum, and particularly magnesium alkyls, stand in clear contradiction to this widely accepted metathesis process. The formation of zinc alkoxides can be rationalized in terms of an intramolecular transformation of zinc alkylperoxides (Scheme ; the proposed η 2 ‐binding mode of alkylperoxide ligand has previously been observed for aluminum and magnesium alkylperoxide complexes).…”
Section: Resultscontrasting
confidence: 99%
“…During the last decade, our group's studies have provided a fresh perspective on such oxygenation processes, and have indicated that, despite the involvement of radical species, a radical‐chain process alone cannot fully explain all of the experimental observations . For example, we have convincingly demonstrated the essential role of both the coordination state of the organometallic species (M=Al, Zn, or Mg) and the geometric requirements of an O 2 molecule approaching the metal center in the case of rationally designed aluminum alkyls . In the latter case, the combined structural and chemical patterns provided compelling experimental evidence that attack of O 2 on the metal center from a desired direction is the key feature in O 2 activation by tetrahedral organoaluminum complexes, prior to insertion of the dioxygen molecule into the Al−C bond .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Other tetranuclear Zn 2+ sites appeared to be embedded in larger complexes that contain up to more than eight Zn 2+ ions. 75,76 …”
Section: Resultsmentioning
confidence: 99%